2012 19th IEEE International Conference on Image Processing 2012
DOI: 10.1109/icip.2012.6467105
|View full text |Cite
|
Sign up to set email alerts
|

Depth map compression using multi-resolution graph-based transform for depth-image-based rendering

Abstract: Depth map compression is important for efficient network transmission of 3D visual data in texture-plus-depth format, where the observer can synthesize an image of a freely chosen viewpoint via depth-image-based rendering (DIBR) using received neighboring texture and depth maps as anchors. Unlike texture maps, depth maps exhibit unique characteristics like smooth interior surfaces and sharp edges that can be exploited for coding gain. In this paper, we propose a multi-resolution approach to depth map compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…In particular, GFT has been successfully used for depth map compression [9], denoising [10], etc. In this paper, we propose to use GFT for expansion hole filling, or more generally, image interpolation.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, GFT has been successfully used for depth map compression [9], denoising [10], etc. In this paper, we propose to use GFT for expansion hole filling, or more generally, image interpolation.…”
Section: Related Workmentioning
confidence: 99%
“…Compared to non-local image interpolation methods [15], the complexity of our GBT interpolation is bounded by the few number of pixels within the neighborhood of an expansion hole used to construct the graph. While GBT has been used for compression of depth maps [16,17], this is the first work in the literature of using GBT for image patch interpolation.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, in [16] potentials of GSP to linear predication, customer behavior prediction, and image compression are demonstrated. GSP, or more specifically, graph Fourier transform, has been used for image compression (depth map coding) and image denoising in [19] and [20], respectively. In [17], the GSP tools are used for dataset classification, where it is shown that the GSP-based classification, as applied to image classification, provides more accurate and more robust results compared to standard support vector machine (SVM) and neural network-based approaches.…”
Section: A Graph-based Signal Processingmentioning
confidence: 99%